2020
DOI: 10.7150/jca.46158
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of PD-L1 and SOCS3 Co-expression with the Prognosis of Hepatocellular Carcinoma Patients

Abstract: Purpose: To investigate the correlation between the expression of PD-L1, SOCS3 and immune-related biomarkers CD276, CD4, CD8 in hepatocellular carcinoma (HCC) and further determine the relationship with clinicopathologic characteristics and the prognostic value of their co-expression in HCC patients. Methods: We assessed the expression of PD-L1, CD276, SOCS3, CD4 and CD8 by immunohistochemistry in tumor tissue from 74 HCC patients who underwent curative hepatectomy. Results: High expression of PD-L1 was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(43 reference statements)
0
12
1
Order By: Relevance
“…Khan et al reported that SOCS3 mRNA expression was significantly lower in HCC than adjacent tissues, yet SOCS3 mRNA expression lacked predictive potential [ 32 ]. However, high expression of SOCS3 protein in HCC patients had better prognosis than that for patients with SOCS3 low-expression [ 33 , 34 ]. In our study, we also demonstrated that HCC patients with high SOCS3 protein expression had a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al reported that SOCS3 mRNA expression was significantly lower in HCC than adjacent tissues, yet SOCS3 mRNA expression lacked predictive potential [ 32 ]. However, high expression of SOCS3 protein in HCC patients had better prognosis than that for patients with SOCS3 low-expression [ 33 , 34 ]. In our study, we also demonstrated that HCC patients with high SOCS3 protein expression had a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, SOCS3 hypomethylation was observed in NSCLC. Previous studies indicated high expression of SOCS3 may be a better prognostic marker in hepatocellular carcinoma [69], gastric cancer [70], and colorectal cancer [71].…”
Section: Discussionmentioning
confidence: 99%
“…OS and PD-L1 expression in cluster 2 was significantly different from that in cluster 1. The better prognosis of cluster 2 patients may be related to the lower expression level of PD-L1 [ 38 ]. GSEA results showed that TGF- β signaling and Hedgehog signaling were significantly enriched in cluster 2.…”
Section: Discussionmentioning
confidence: 99%